Philosophy Tri Kaya Parisudha As Moderators The Effect of Love of Money And Self Efficacy on Ethical Behavior of Tax Consultant - I Gusti Putu Eka Rustiana Dewi; I Gede Cahyadi Putra (Journal Research of Social Science, Economics, and Management, 2022)
The purpose of the study is to determine whether the philosophy of tri kaya parisudha, also known as Balinesse local wisdom, will be able to lessen the effect of love of money and strengthen self-efficacy on tax consultant's behavior. The study also aims to determine whether the relationship between love of money and self-efficacy and ethical behavior of tax consultant. The study was done in response to the phenomena of bribery cases that involved tax advisors, tax payers, and government tax officers, adding to the list of corruption cases in Indonesia. Samples for the research's data collection include registered tax consultants in Bali who were surveyed utilizing a questionnaire. The result show that self-efficacy and love of money have a positive significant impact on tax consultants' ethical behavior and a negative significant impact on each other. Tri Kaya Parisudha philosophy has the ability to strengthen self-efficacy and weaken the impact of love of money on tax consultants' ethical behavior.